Effect of Using Hormone Oosit Developer (Oodev) Through Feed on Platy Fish (Xiphophorus sp.) Against Performance Reproduction - Perdana, Rangga Putra; Marzuki, Muhammad; Scabra, Andre Rachmat (Jurnal Media Akuakultur Indonesia, 2024)
Platy fish is freshwater ornamental fish which has beautiful color so it has high aesthetic and economic value, belonging to a type of fish called the â€œlive bearerâ€ or having the ability to give birth. Current problem faced by platy fish farmers are the low production to meet the rising market demand. This causes the lack of ability to reach the desired production target. This research evaluate the effect of giving Oodev through feed to the amount of production of larvae platy fish Xhiphophorus sp. with different dose. The research used completely randomized design with treatment of different Oodev dose which were P1 (0 ml/kg fish), P2 (0,5 ml/kg fish) P3 (1,0 ml/kg fish) and P4 (1,5 Mml/kg fish) each repeated three times. Oodev hormone was given through feed two times a day with feeding rate (FR) 3%. Results showed that the giving of OODEV could raise the number of larvaes produced by female parent with the highest number of 29,33 larvaes on the P3 and lowest treatment as much as 15 larvaes at P1 (P<0,05). The number of larvae produced by the female parent P3 treatment provides the best results with total larvae amount of 176 or average each treatment of 58,76 larvaes.